Tidal Effect on Coastal Municipal Drainage System: Case Study of Bandar Maharani, Muar - Abdul Rahman, Nazri; Jamaludin, Mohd Safri; Tan, Lai Wai; Md Ali, Zarina; E. Pinilla, Camilo (International Journal of Integrated Engineering, 2022)
Flash flood at Bandar Maharani, Muar is a common occurrence. Although, numerous studies and continual improvement to drainage systems have been carried out, flash flood at Bandar Maharani still persists. Aim of this study is to assess tidal effect on effectiveness of Bandar Maharani drainage system. 80% of the 12.25 km area of Bandar Maharani consists of residentials and commercial buildings. Capacity of drainage system along 15 major roads in Bandar Maharani has been evaluated. Peak flows due to 5, 10, 50 and 100-year ARI rainfall were considered. High tide which occurred in 1999 has been used to investigate the effect of tides on capacity of drain along Jalan Bakri. It has been shown that high tide has reduced as much as 32% of capacity of drains along Jalan Bakri, a major drainage system of Bandar Maharani. The effect of tides can reach as far as 3.687 km upstream. This means that when high tides and heavy rain occur concurrently, capacity of drains along Jalan Bakri will be affected, thus lead to flash floods.